The Effect of Using Demineralized Whey Powder and Buttermilk Powder Instead of Skimmed Milk Powder on Physicochemical, Microbiological, and Biochemical Properties of Yogurt - Kucuk, Neslihan Yildiz; Bakirci, Ihsan (Wiley, 2025)
This study aimed to increase the total solids amount of raw milk by adding demineralized whey powder (d-WP), buttermilk powder (BMP), and skimmed milk powder (SMP) thereby producing yogurt with improved physicochemical, microbiological, and biochemical properties. d-WP and BMP were mixed with SMP at seven different ratios to produce yogurt. The physicochemical, microbiological, and biochemical properties of the yogurt samples (A, B, C, D, E, F, G) were analyzed during the storage period (28 days). Sample B (3.0% SMP, 0.5% d-WP, 0.5% BMP) has the highest results for viscosity and water-holding capacity, while sample C (2.0% SMP, 1.0% d-WP, 1.0% BMP) has the lowest acidity and highest pH. The concentrations of orotic, hippuric, and propionic acids in yogurts were determined to be statistically significant (p< 0.01). All 20 amino acids were detected at different ratios in all yogurt samples. It was determined that G (2.0% SMP, 2.0% d-WP) had the highest total amino acid content and F (2.0% SMP, 2.0% BMP) had the lowest total amino acid content during the storage period. It was determined that acetaldehyde (21.53 +/- 2.27 mmol kg(-1)), which creates the typical aroma of yogurt, was produced more in sample D containing 1.0% SMP, 1.5% d-WP, 1.5% BMP. Using d-WP and BMP in appropriate combinations (0.5-1.5%) with SMP can produce a more functional yogurt with higher nutritional value, without causing any negative effects on the physicochemical, microbiological, and biochemical properties of yogurt.
Keywords: amino acid profile; aroma compounds; buttermilk powder; demineralized whey powder; organic acid profile; yogurt